When corporate accountability meets transitional justice : international law and national practice / Taygeti Michalakea. - Michalakea, Taygeti (Cambridge University Press, 2025)
Corporate malfeasance is omnipresent in conflict and repression situations around the world, but efforts for corporate accountability by transitional mechanisms have been dispersed, meagre and unsuccessful. This book analyses the legal rationale behind integrating corporate accountability within the unique context of transitional justice, tracing these issues across international and national legal regimes. It offers a systematic inquiry into the precise legal possibilities and operational limits of access to remedy for victims of corporate abuses in transitions, and the corresponding obligations of states as designers of transitional measures. Providing a systematic and consolidated legal account of the convergence of corporate accountability and transitional justice, the book sketches a new imaginary of transitional justice, rooted in transformative approaches. It will be a valuable resource for academics andjudicial and institutional actors, as well as victims and practitioners in the field of transitional justice and post-conflict reconstruction.